ANALISIS GAYA BAHASA (HIYU) PADA LIRIK LAGU SEKAI NO OWARI DALAM ALBUM ENTERTAINMENT - Anggia Febrianti; Hermandra Hermandra; Zuli Laili Isnaini (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This study aimed to describe language style in lyrics from band sekai no owari in entertainment album. This thesis discusses about the language styles occurred in Tarigan’s thory (2009) and stylistic. The purpose of this research is to understand the style language and know the meaning of the song. The method used in this research is qualitative descriptive and used style language theory and stylitics. In collecting data, this research used heed method with technique of free heed “libat cakap”and catat. The result of this research are 44 data style of language, containing simile, metaphor, personification, depersonification, allegory, antithesis, tautology, hyperbole, lythotes, oxymoron, clymax, metonymy, eufimisme, erothesis, paralelysme, asyndeton, polisintedon, alliteration, asonomansia dan anaphora.Keywords: Language Style, Stylitics, Lyrics, Sekai No Owari, Entertainment Album